2017
DOI: 10.18203/2394-6040.ijcmph20170264
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of mother in childbearing age with BMI <18.5 kg/m2 and has heterozygous variant D327N SHBG genotype (w/v)

Abstract: Background: Body mass index (BMI) determined by genetic and environmental factors. One of the genetic factors that determine the BMI is a genetic polymorphism of sex hormone binding globulin (SHBG), whereas the intake of nutrients is one of the environmental factors. The objective: investigate to macronutrient intake of mother in childbearing age with BMI <18.5 kg/m2 and has heterozygous variant D327N SHBG genotype (W/v).Methods: Anthropometric measurement, genotyping of D327N SHBG gen exon 8, and three day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…In detail, that differences of dietary intake at mother in childbearing age with BMI <18.5 kg/m 2 and has heterozygous variant SHBG genotype (W/v) determine to status of chronic energy deficiency (CED), therefore that low protein, fat and carbohydrate intake then getting low of CED status. 15 We suspect that beside of genetic factor, environment factor such as dietary intake also affected to ACG. Because that too need of ACG reports from genetic aspect and dietary intake.…”
Section: Introductionmentioning
confidence: 98%
“…In detail, that differences of dietary intake at mother in childbearing age with BMI <18.5 kg/m 2 and has heterozygous variant SHBG genotype (W/v) determine to status of chronic energy deficiency (CED), therefore that low protein, fat and carbohydrate intake then getting low of CED status. 15 We suspect that beside of genetic factor, environment factor such as dietary intake also affected to ACG. Because that too need of ACG reports from genetic aspect and dietary intake.…”
Section: Introductionmentioning
confidence: 98%
“…This is in accordance with research that shows that subjects with a BMI of <18.5 kg/m 2 actually have a low intake of macronutrients (proteins, fats, and carbohydrates), resulting in chronic energy deficiency with a low status. 46…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that subjects with BMI <18.5 kg/m2 actually had a low intake of macronutrients (protein, fat, and carbohydrates), resulting in chronic energy deficiency with low status. (93) Based on the results of this study, the intake of macronutrients must be met so that the elderly do not experience chronic energy deficiency and their quality of life becomes better.…”
Section: Systematic Review and Metaanalysismentioning
confidence: 98%